2001
DOI: 10.2307/3094830
|View full text |Cite
|
Sign up to set email alerts
|

From the Bottom Up? Technical Committee Activity and Alliance Formation

Abstract: and Rosemarie Ham Ziedonis, as well as seminar participants at Duke, Harvard, Maryland, Northwestern, NYU, and Wharton. We are especially grateful to Christine Oliver and the three anonymous reviewers for comments that greatly improved the paper, as well as Linda Johanson for her masterful copy editing We are indebted to Elaine Baskin, publisher of Communications Standards Review, for providing roster data from back issues in electronic form. We also appreciate the cooperation of Susan Hoyler and Eric Schimmel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
209
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 288 publications
(216 citation statements)
references
References 41 publications
7
209
0
Order By: Relevance
“…This has been confirmed in studies focusing on ties originating from previous exchanges among leaders (Barden and Mitchell 2007), executives' previous jobs (Eisenhardt andSchoonhoven 1996, Kim andHiggins 2007), and interlocking directorates (Gulati and Westphal 1999). Research has focused mostly on senior executives, but midlevel managers participating in technical committees (Rosenkopf et al 2001) and other boundary spanners engaged in interorganizational exchanges have also been found to aid the formation of interorganizational ties (Barden and Mitchell 2007).…”
Section: Embeddedness In Interorganizational and Interpersonal Networkmentioning
confidence: 57%
See 4 more Smart Citations
“…This has been confirmed in studies focusing on ties originating from previous exchanges among leaders (Barden and Mitchell 2007), executives' previous jobs (Eisenhardt andSchoonhoven 1996, Kim andHiggins 2007), and interlocking directorates (Gulati and Westphal 1999). Research has focused mostly on senior executives, but midlevel managers participating in technical committees (Rosenkopf et al 2001) and other boundary spanners engaged in interorganizational exchanges have also been found to aid the formation of interorganizational ties (Barden and Mitchell 2007).…”
Section: Embeddedness In Interorganizational and Interpersonal Networkmentioning
confidence: 57%
“…For example, endogenous network dynamics cannot explain how to access networks without having a prior position in them (Rosenkopf et al 2001). Indeed, process studies of organizational network dynamics found intentional network design alongside pathdependent network development mechanisms (Doz et al 2000, Koza and Lewin 1999, Sydow 2004).…”
Section: Dynamics In Interorganizational Networkmentioning
confidence: 99%
See 3 more Smart Citations